UPAYA GURU PENDIDIKAN KEWARGANAGARAAN DALAM MENANAMKAN NILAI-NILAI KARAKTER RELIGIUS PADA SISWA KELAS VIII SEKOLAH MENENGAH PERTAMA TUNAS MUDA KECAMATAN SUNGAI RAYA KABUPATEN KUBURAYA - Octavia, Erna (Lambung Mangkurat University Indonesia, 2016)
Globalization has brought widespread impact in the outside world, not least in our country. The impact of globalization there is a positive, and the negative impact of which is violence, drug abuse, promiscuity and crime. All the negative things that led to the loss of the nations character. In addition, the character of the young generation is already at an alarming point. The morality of this nation has been separated from the norm, ethics, religion, and culture sublime, so sex becomes a phenomenon without being in the slightest weir. Sugeng (Asmani, 2011: 23) states that